VARIABLES THAT INFLUENCE TAX AVOIDANCE OF FINANCIAL SECTOR COMPANIES LISTED ON THE IDX - Verin, Verin; Santioso, Linda (International Journal of Application on Economics and Business, 2024)
Tax revenue has increased every year, so the government must encourage tax compliance activities so that community welfare and development can be realized. The government must ensure that there are no tax avoidance practices carried out by taxpayers given the application of the self-assessment collection system in Indonesia. This study aims to determine how executive character, executive compensation, institutional ownership, independent commissioners, and accounting conservatism have an impact on the tax avoidance of financial sector companies listed on IDX. The technique that was used in this research is purpose sampling with the results of about 25 financial sector companies listed on the IDX. In this research, multiple linear regression analysis testing was carried out using the SPSS IBM Statistics program. The results obtained from this study confirm that executive character has a significant and positive influence on tax avoidance, on the other hand, executive compensation, institutional ownership, independent commissioners, and accounting conservatism do not have a significant effect on tax avoidance. According to this study, companies should show more attractive environmental performance to attract investors.